Traditional urban Persian Square as a sense of place - case study of Naqsh-E-Jahan Square Isfahan, Iran / Arash Asgharian - Asgharian, Arash (2013)
Urban squares are active elements of a city, and are continuously changing according to social, economic, and technical conditions. They can be considered ideal places to display artifacts and components that remind people of their shared experiences and what they value as a community having a strong sense of place. Focusing on public spaces is the first step to any study of a city and its society with a strong sense of place. Some traditional urban squares such as Naqsh-e-Jahan in Iran have all the essential elements to create the sense of place for visitors. This research aims to explore the specific characteristics that enhance space quality. In addition, it tries to find the organizational factors in the traditional urban landscape such as Naqsh-e- Jahan in promoting the quality of designed public space through survey with focused on the concepts of sense of place. Mixed quantitative and qualitative research methods were adopted to identify urban squares in Persia, their significance as traditional urban landscapes, their characteristics especially those that increase the quality of urban spaces and create sense of place. Empirical data for quantitative research was collected via a questionnaire survey in Naqsh-e-Jahan square and qualitative data via in-depth structured interviews. The findings revealed that factors such as attention to users and climate and involving all the visitors’ sense and attending to physical factors had an effect on increasing the sense of place.